Transglutaminase 2 affinity and enzyme‐substrate intermediate stability as determining factors for T‐cell responses to gluten peptides in celiac disease. Issue 9 (13th July 2022) - Amundsen, Sunniva F.; Stamnaes, Jorunn; du Pré, Marie Fleur; Sollid, Ludvig M.
Abstract: The adaptive immune response of celiac disease (CeD) involves presentation of gluten peptides to CD4 + T cells by transglutaminase 2 (TG2) specific B cells. This B‐cell/T‐cell crosstalk is facilitated by involvement of TG2:gluten peptide complexes that act principally in the form of enzyme‐substrate intermediates. Here, we have addressed how gluten peptide affinity and complex stability in the presence of secondary substrates affect the uptake of TG2:gluten peptide complexes by TG2‐specific B cells and the activation of gluten‐specific T cells. We studied affinity of various gluten peptides for TG2 by biochemical assay, and monitored uptake of gluten peptides by TG2‐specific B cells by flow cytometry. Crosstalk between TG2‐specific B cells and gluten‐specific T cells was assayed with transfectants expressing antigen receptors derived from CeD patients. We found that gluten peptides with high TG2 affinity showed better uptake by TG2‐specific B cells. Uptake by B cells, and subsequent activation of T cells, was negatively affected by polyamines acting as secondary TG2 substrates. These results show that affinity between gluten peptide and TG2 governs the selection of T‐cell epitopes via enhanced uptake of TG2:gluten complexes by TG2‐specific B cells, and that exogenous polyamines can influence the CeD immune responses by disrupting TG2:gluten complexes. Abstract : Key immunological processes in celiac disease involve interaction between transglutaminase 2 (TG2)‐specific B cells and gluten‐specific T cells. The outcome of these processes is governed by the affinity between different gluten peptides and the enzyme (I) as well as by the presence of secondary TG2 substrates (II).